Behaviour of plain concrete beam under half-sine impulse load / Zulkifli Samsudin (Faculty of Civil Engineering, 1997)
High strength concrete is not fundamentally different from normal strength concrete, it is different only in its level of strength and associated properties. Research in high strength concrete (HSC) has been identified as priority field of study world wide. As research progresses, and industry gears itself to production, the use of high strength concrete is set to greatly expand in the twenty-first century. Though we are very familiar with the HRC, its behaviour due to dynamic load is not fully understood. Therefore, as a bench mark, stud}' of plain concrete beam behaviour due to impulsive load in the form of half sine load as well as static loading with respect to the serviceability and ultimate limits will be undertaken. Three beams , sizing 125mm x 150mm x 1400mm , have been tested. One of the beam is loaded with static loading conditions and tested until failure in order to achieve the yield strength of the beam. Whilst two more beams are tested under half sinusoidal repeated constant amplitude load with the maximum and minimum loads being 60% and 50% of the yield load respectively. Deflection and cracks behaviour are studied and compared with the previous work. In the static loading test, there are three stages of response between load and deflection. For dynamic loading there is no increase in deflections after the load reached 10,000 cycles and it is believed that plain concrete beam exhibit a fatigue endurance limit.